The Concept of the Heat Removal System of a High-Flux Research Reactor - Vitaly Uzikov; Ildar Suleimanov; Irina Uzikova (Science and Technology of Nuclear Installations)
Achieving high neutron fluxes in research pressurized water reactors is directly related to the intensity of the coolant flow through the core and the pressure in it, which provides an increased saturation temperature and a margin to critical heat flux. Therefore, it is practically impossible to provide very high neutron fluxes in pool-type reactors, especially in the case of downward movement of the coolant in the core. At the same time, vessel-type research reactors (for example, SM-3 and HFIR) make it possible to achieve neutron flux densities up to 4 × 1015 n/(cm2 s), but at the same time, the risks of core degradation in case of violations in the heat removal system become quite high. The proposed concept of a heat removal system for a high-flux reactor facility combines the increased reliability of safe heat removal from the core and the convenience of handling irradiation cells, for example, in the production of isotopes. The concept provides for the location of a compact core in a pressurized vessel and the placement of a neutron reflector around the vessel in the reactor pool. Cooling of the reactor core in the housing and the irradiation channels in the neutron reflector is carried out by different systems of forced circulation of the coolant. At the same time, at the shutdown reactor, after opening the natural circulation valves, safe heat removal from the reactor core and the neutron reflector can be carried out by the water of the reactor pool. However, even with a complete failure of all forced circulation circuits, the evaporation of water from the surface of the pool makes it possible to safely remove the residual heat from the fuel assemblies and from the irradiation devices in the cells of the reflector.